Analysis of the Influence of Factors Affecting Purchase Intention of Premium Items in MOBA-Type Online Games - Andri Ardhiyansyah; Favian Firwan Firdaus; Bayu Aji Aritejo (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
Increased mobile gaming revenue can’t be separated from the rapid growth of technology, especially on smartphones. The popularity of free-to-play games also supports the increase in mobile gaming revenue. The Mobile Legends and AoV, games with Multiplayer Online Battle Arena type, are popular today, where they can be played on any smart phone anywhere and anytime. One of the main commodities in this game is the premium items. to get the virtual goods players have to exchange some money that can be purchased through google play store or electronics stores. The purpose of this research is to analyze the effect of enjoyment value, character competency value, visual authority value, monetary value, character identification, and the satisfaction of the game against the intention of repurchase. This research uses survey method to collect data. The Sampling method is non- probabilities with purposive sampling approach. The number of samples in this study is 130 respondents, with the criteria playing a Mobile Legends or AoV and make purchases of premium items on the games. Hypothesis testing was analyzed using multiple linier regression. The result of hypothesis testing shows that the six independent variables, namely the value of pleasure, the value of character competence, the value of visual authority, the value of money, the character identification, and the satisfaction of the game have a positive effect on the intention of repurchasing premium items.